Pengaruh Service Quality, Product Quality, dan Iklan Terhadap Nasabah BNI - Badriatin, Tine; Wursan; Kurniawan; Sani, Ageng Asmara (Forum Kerjasama Pendidikan Tinggi, 2023)
Customer satisfaction is the ultimate goal of a service process carried out by both government and private agencies. This research originates from the existence of various problems in the field which indicate that customer satisfaction is still not optimal. This is indicated by the amount of funds collected when viewed from the debit balance, which has fluctuated. This shows that the level of satisfaction has also fluctuated. Factors that influence customer satisfaction, including service quality, product quality and advertising. The purpose of this study was to determine and describe the effect of service quality, product quality and the effect of advertising on customer satisfaction at BNI Tasikmalaya Branch. The research was conducted using a quantitative descriptive method, namely by making a systematic, factual and accurate description of facts or the nature of objects and interpreting the relationship between the phenomena investigated. The total population is 113 while the sample is 50 using the slovin technique. The tool for collecting data is a questionnaire and the data analysis that is sought is correlation, determination. T test and F test. The conclusion shows that simultaneously service quality, product quality, advertising. has an effect on customer satisfaction, and partially service quality has an effect on customer satisfaction, product quality has an effect on customer satisfaction, and advertising has an effect on customer satisfaction. Each influence is declared significant. Based on correlation calculations, it is known that the correlation obtained from service quality, product quality and advertising on customer satisfaction is 80.9%. This shows that service quality, product quality and advertising have a strong influence on customer satisfaction.